2002
DOI: 10.1002/j.1939-4640.2002.tb02345.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Androgen and Estrogen Receptors in Adult Male Mouse Reproductive Tract

QING ZHOU,
RONG NIE,
GAIL S. PRINS
et al.

Abstract: There is considerable variation, both within and between species, in reports of nuclear steroid receptor localizations in the male reproductive tract. In this study, androgen receptor (AR) and estrogen receptors ERα and ERβ were visualized by immunohistochemistry in adult male mice reproductive tracts, including testes, efferent ductules; initial segment, caput, corpus, and cauda epididymides; and vas deferens. Antibody specificity was demonstrated by Western blot and antibody competition. In testis, AR was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(5 citation statements)
references
References 88 publications
0
4
0
1
Order By: Relevance
“…In particular, the presence of GPER in pachytene spermatocytes and round spermatids could be hypothesized to be related to an activation of the epidermal growth factor receptor/extracellular signal-regulated kinases (EGFR/ERK) pathway, which is involved in the transcriptional modulation of genes controlling apoptosis and differentiation [ 25 , 26 ]. For ERs’ localization, it was reported that ER-alpha and ER-beta are expressed in the testicular germ cells in some animal species including dogs, rodents, and humans, with some differences in their protein distribution [ 32 , 34 , 35 , 46 , 47 ]. According to our findings, GPER is co-expressed only with ER-alpha in round spermatids, suggesting their involvement in the regulation of spermiogenesis, while the localization of ER-beta in Sertoli cells supports germ cell maturation through the supply of different mediators including estrogens, which could be indicative of this function in these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the presence of GPER in pachytene spermatocytes and round spermatids could be hypothesized to be related to an activation of the epidermal growth factor receptor/extracellular signal-regulated kinases (EGFR/ERK) pathway, which is involved in the transcriptional modulation of genes controlling apoptosis and differentiation [ 25 , 26 ]. For ERs’ localization, it was reported that ER-alpha and ER-beta are expressed in the testicular germ cells in some animal species including dogs, rodents, and humans, with some differences in their protein distribution [ 32 , 34 , 35 , 46 , 47 ]. According to our findings, GPER is co-expressed only with ER-alpha in round spermatids, suggesting their involvement in the regulation of spermiogenesis, while the localization of ER-beta in Sertoli cells supports germ cell maturation through the supply of different mediators including estrogens, which could be indicative of this function in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…As known, estrogens have an important role in maintenance of some aspects of epididymal physiology [ 14 ]. The expression of ERs has been widely documented in the epididymis of several species (mice, rats, dogs, cats, and monkeys) [ 32 , 35 , 36 , 46 , 58 ] with a common observation of the presence of ER-alpha in the efferent ductules that not only provide to the reabsorption of more than 90% of the rete testis fluid but concentrate sperm for epididymal storage [ 59 ]. In addition, the very wide GPER expression in the epididymis of pigs [ 28 , 60 ], rats [ 30 ], sheep [ 61 ] and in humans’ ductuli efferents and proximal epididymis [ 29 ] suggests its involvement in sperm maturation, protection, and storage.…”
Section: Discussionmentioning
confidence: 99%
“…Several estrogen receptors mediate the effects of estrogens in the testis. In rodents, ERα was found in Leydig cells and peritubular myoid cells, ERβ was found in Sertoli cells and some germ cells (spermatogonia, spermatocytes) and GPER was detected in Leydig cells, Sertoli cells and germ cells (spermatocytes, spermatids) (37)(38)(39)(40)(41). Faah, encoding a hydrolase that promotes Sertoli cell survival by degrading anandamide, is a direct target gene of estrogens in mature Sertoli cells (42,43).…”
Section: Two Distinct Populations Of Leydig Cells Appear During Mouse...mentioning
confidence: 99%
“…Several estrogen receptors mediate the effects of estrogens in the testis. In rodents, ERα was found in Leydig cells and peritubular myoid cells, ERβ was found in Sertoli cells and some germ cells (spermatogonia, spermatocytes), and GPER was detected in Leydig cells, Sertoli cells, and germ cells (spermatocytes, spermatids) (Zhou et al, 2002;Kotula-Balak et al, 2018;Lucas et al, 2010;Chimento et al, 2010;Chimento et al, 2011). Faah, encoding a hydrolase that promotes Sertoli cell survival by degrading anandamide, is a direct target gene of estrogens in mature Sertoli cells (Grimaldi et al, 2012;Rossi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%